2014
DOI: 10.1111/jai.12629
|View full text |Cite
|
Sign up to set email alerts
|

Stock structure analysis of ‘Bombay duck’ (Harpadon nehereusHamilton, 1822) along the Indian coast using truss network morphometrics

Abstract: Summary Harpadon nehereus, commonly known as ‘Bombay duck’, is a fish with a discontinuous distribution along the Indian peninsula. The fisheries are dominant on the north‐east and north‐west coast but are absent in commercial landings below 15° north latitude. Heretofore stock assessment studies had not considered the various spawning stock components that replenish this fishery, therefore the present study. Fish samples were collected from four locations: two each from the northeast and the northwest coasts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Morphological differences in factor 1 of A. Clupeoides could be due to its feeding behavior as for predator evasiveness and foraging adeptness, high locomotory performance is crucial (Chipps, Dunbar, & Wahl, 2004;Swain, Hutchings, Foote, Cadrin, & Friedland, 2005). For taking the optimum amount of food, body depth adaptations are essential for transient and topical swimmers (Pazhayamadom et al, 2014). It is reported that the deep healthy fish stocks from less turbulent waters perform faster speed with brief propulsion (Blake, 2004;Webb, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological differences in factor 1 of A. Clupeoides could be due to its feeding behavior as for predator evasiveness and foraging adeptness, high locomotory performance is crucial (Chipps, Dunbar, & Wahl, 2004;Swain, Hutchings, Foote, Cadrin, & Friedland, 2005). For taking the optimum amount of food, body depth adaptations are essential for transient and topical swimmers (Pazhayamadom et al, 2014). It is reported that the deep healthy fish stocks from less turbulent waters perform faster speed with brief propulsion (Blake, 2004;Webb, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient degree of isolation may result in notable morphological, meristic, and shape differentiation among stocks of a species which may be recognizable as a basis for identifying the stocks. The characteristics may be more applicable for studying short-term, environmentally induced disparities, and the findings can be effectively used for improved fisheries management [18][19][20][21]. The truss network system can effectively be used to distinguish between the hatchery and wild stocks.…”
Section: Truss Network Measurementsmentioning
confidence: 99%
“…Although many researchers now use geometric morphometric (GM) methods (Zelditch et al, 2004) such as the thin-plate spline and relative warp analysis to study shape, MM is still used, for example, for fish stock identification (e.g. AnvariFar et al, 2011;Sajina et al, 2011;Kohestan-Eskandari et al, 2014;Pazhayamadom et al, 2015). Richtsmeier et al (2002) presented many of the assumptions, benefits, and liabilities of GM and MM.…”
Section: Discussionmentioning
confidence: 99%